(untitled) (Fiep Bulletin - online, 2013)
The interpessoal relationship amons two kinds of people a man and a woman - from a is born a family. People that joined and they built a history that can be observed in first (1st) and third (3rd) person. This study looked for identify the perspectives in 1st and 3rd person of senior couples. To 1st person of the singular it corresponds to the me, body Image, and the way as we see the other starting from ours lives personal, we attributed to 3rd singular person, or vision interpessoal. They were part of the academics’ of the 3rd adult age research 5 couples, with 60 years or more. The methodology that was used was individual, semi-structured, with 10 questions for content analysis, where they were classified, in 1st and 3rd person and divided in categories, which were worked in the form of indicators and analyzed in agreement with the gender. The result of the perspective in 1st person points the commitment as main reason for the affection in the masculine gender. In the feminine, the commitment continues being a fort reason for the affection, however, the conduct was very taken seriously. In relation to the marriage, the masculine gender saw it as a stable relationship, for the womans, already the maureage is something indissoluble. And the main pointed reasons for duration of that union went both genders the love and the children. Already the perspectives in 3rd person, the results for both genders were similar, where they were pointed positive virtues, without exaltation of defects and the verification of the learning construction with the coexistence. This way, we can notice the several facets of the marriage and to verify that the relationship among two people is something complex, that it demands understanding and donation of both parts, and when being analyzed through their own agents’ perspectives, we can understand it how intimate and subjective it is the marriage.